2013
DOI: 10.2166/wst.2013.313
|View full text |Cite
|
Sign up to set email alerts
|

Bentonite for ciprofloxacin removal from aqueous solution

Abstract: Ciprofloxacin hydrochloride (CIP) is the second generation of fluoroquinolone antibiotics whose residues are found in wastewater and surface water. CIP has high aqueous solubility under different pH conditions and high stability in the soil system. In this study, bentonite was used as a potential sorbent for the removal of CIP from aqueous solutions using batch experiments. The effects of various parameters such as contact time, pH, adsorbent dosage, agitation speed, ionic strength and initial concentration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(37 citation statements)
references
References 0 publications
2
32
0
1
Order By: Relevance
“…55, 7.4, 33, 112, 135, and 300 mg of CPX per gram of adsorbent by modified coal fly ash, kaolinite, illite, carbon xerogel, rectorite, carbon nanotubes and activated carbon, respectively Wang et al, 2011;Zhang et al, 2011;Carabineiro et al, 2012). However, the results obtained for adsorption of CPX on montmorillonites showed higher adsorption capacities Genç et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…55, 7.4, 33, 112, 135, and 300 mg of CPX per gram of adsorbent by modified coal fly ash, kaolinite, illite, carbon xerogel, rectorite, carbon nanotubes and activated carbon, respectively Wang et al, 2011;Zhang et al, 2011;Carabineiro et al, 2012). However, the results obtained for adsorption of CPX on montmorillonites showed higher adsorption capacities Genç et al, 2013).…”
Section: Introductionmentioning
confidence: 92%
“…These adsorbents have not only proved to be effective, but also widely distributed, affordable and environmentally friendly materials (Grassi et al, 2012). Consequently, clay minerals have been applied for the removal of many different organic compounds as dyes (Rytwo et al, 2000), pesticides (Polatti et al, 2006) and antibiotics (Putra et al, 2009;Molu and Yurdakoç, 2010;Genç et al, 2013). Particularly, the bentonites located in the Alto Valle de Río Negro-Neuquén, Argentina have showed to be good adsorbents for the removal of thiabendazole fungicide (Roca and the tetracycline antibiotic (Parolo et al, 2008) from aqueous media.…”
Section: Introductionmentioning
confidence: 99%
“…When the solution pH is above 8.89, the anionic form CIPRO -prevails due to loss of a proton from the carboxylic group. When solution pH is between 5.90 and 8.89, the zwitterionic form CIPRO 0 resulting from the charge balance of the two groups mentioned above is the dominant species (Genç at al., 2013). The physico-chemical properties of CIPRO were summarized in Figure 1.…”
Section: Aqueous Solutionsmentioning
confidence: 99%
“…CIPRO concentrations between 0.7 and 124.5 µg l -1 in hospital effluent (Jiang et al, 2012;Genç et al, 2013), between 249 and 405 ng l -1 in wastewater treatment plants have been reported (Zaviska et al, 2013). CIPRO was found in wastewater treatment plant effluents at concentrations of 313-568 ng l -1 and up to 124.5 µg l -1 in hospital sewage water (De Witte et al, 2009).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation